2021
DOI: 10.15789/2220-7619-ndo-1485
|View full text |Cite
|
Sign up to set email alerts
|

New data on the level of immune stratum against Q fever agent in population of the of Republic of Guinea

Abstract: Резюме. Коксиеллез (лихорадка Ку)-общее для человека и животных природно-очаговое заболевание, возбудителем которого являются бактерии вида Coxiella burnetii. Один из факторов, показывающих возможность циркуляции патогена на определенной территории-наличие иммунной прослойки у жителей региона. Изучение иммунной структуры населения Гвинейской Республики в отношении коксиеллезов началось в 80-е годы. прошлого столетия. Настоящее исследование проводилось в 2015-2019 гг. с целью получения новых сведений об уровне … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Coxiella burnetii is a gram-negative bacterium that resides within cells and is responsible for causing Q fever [ 39 ]. This infectious disease can be transmitted to humans through the consumption of contaminated products or the inhalation of aerosols containing the bacteria [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coxiella burnetii is a gram-negative bacterium that resides within cells and is responsible for causing Q fever [ 39 ]. This infectious disease can be transmitted to humans through the consumption of contaminated products or the inhalation of aerosols containing the bacteria [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with previous studies that have reported the presence of C. burnetii in ticks in Africa [ 47 ] and contribute to our understanding of its circulation in RG. Previously, epidemiological data on this bacterium in RG had been limited to the detection of bacterium-specific antibodies in humans and animals [ 39 , 48 ]. Furthermore, we confirm earlier observations that C. burnetii can be found in ticks collected from small mammals [ 7 , 49 ].…”
Section: Discussionmentioning
confidence: 99%